Embolization of a Duodenal Arteriovenous Malformation in Hereditary Hemorrhagic Telangiectasia: Case Report and Review of the Literature - Phil Inouye; Norman Marcon; Robin A Pugash; Robert H Hyland; Marie E Faughnan (Canadian Journal of Gastroenterology)
A 68-year-old man with hereditary hemorrhagic telangiectasia presented with recurrent, intermittent gastrointestinal hemorrhage. Transfusion of a total of 27 units of red blood cells was required over the three months before admission. Upper and lower endoscopy did not reveal a source of bleeding and a technetium-labelled red blood cell scan was noncontributory. Angiography demonstrated a duodenal arteriovenous malformation originating from a superior mesenteric artery branch. Embolization of the arteriovenous malformation was performed with resolution of gastrointestinal hemorrhage and reduced requirement for blood transfusion. The utility of trans-catheter embolization in the management of duodenal arteriovenous malformations in hereditary hemorrhagic telangiectasia is discussed.